PENGARUH JOB SATISFACTION DAN JOB EMBEDDEDNESS TERHADAP TURNOVER INTENTION - Priyadi, Dhisa Tania (JUIMA : JURNAL ILMU MANAJEMEN, 2025)
Human resources play a strategic role in organizational development. All actions taken by an organization to achieve a goal depend on the human resources. Achieving organizational goals is influenced not only by the strategic position of each human resource but also by their loyalty. Turnover intention is the final stage in the decision making process before an employee leaves an organization. Among the factors influencing turnover intention are job satisfaction and job embeddedness. This study aims to examine the influence of job satisfaction and job embeddedness on turnover intention. The method used was a systematic literature review. The results of a total of five journals used as references in the literature review found that four journals stated that job embeddedness had a significant influence on turnover intention. The journals that stated that job embeddedness did not have a significant influence on turnover intention were because employees could assess the company's performance and how the company could provide opportunities for employees to develop, which would reduce the desire for turnover. Four journals found that job satisfaction significantly influences turnover intention. The primary factor that keeps generation Y in an organization is the fit dimension of job embeddedness, where employees perceived compatibility with the organization and its environment is a key factor in their retention. Organizations must align generation Y's expectations with the reality of their work to improve job satisfaction. Future research is expected to utilize more varied variables and more specific research subjects.